Applications of venturi principle to water aeration systems - Baylar, Ahmet; Ozkan, Fahri (Springer, 2006)
The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. Aeration can increase dissolved oxygen when levels become deficient. Hydraulic structures can significantly improve dissolved oxygen levels by creating turbulent conditions where small air bubbles are carried into the bulk of the flow. Recent researches have focused on developing measurement and predictive techniques for oxygen transfer at hydraulic structures to maintain and enhance water quality. However, reviewing existing studies on aeration performance of hydraulic structures, it seems that there are not too many studies on venturi aeration. The present paper shows applications of venturi principle to water aeration systems. The aeration characteristics of venturi nozzle, venturi conduit and venturi weir are analyzed. The results indicate that venturi aeration might contribute significantly to air entrainment and aeration efficiency. Therefore, venturi device can be used as highly effective aerator in aeration processes.
Keywords: aeration efficiency; air entrainment; conduit; nozzle; venturi; weir